2019
DOI: 10.3390/polym11122010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crystalline Structural Differences Between α- and β-Chitosan on Their Nanoparticle Formation Via Ionic Gelation and Superoxide Radical Scavenging Activities

Abstract: α- and β-Chitosan nanoparticles were obtained from shrimp shell and squid pen chitosan with different set of deacetylation degree (%DD) and molecular weight (MW) combinations. After nanoparticle formation via ionic gelation with sodium tripolyphosphate (TPP), the % crystallinity index (%CI) of the α- and β-chitosan nanoparticles were reduced to approximately 33% and 43% of the initial %CI of the corresponding α- and β-chitosan raw samples, respectively. Both forms of chitosan and chitosan nanoparticles scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 41 publications
(109 reference statements)
6
33
0
Order By: Relevance
“… 17 , 56 , 57 The peak at 2θ ≈ 9–11° corresponds to amide I (−N–CO–CH 3 ), while the peak at 2θ ≈ 19–20° corresponds to amide II (−NH 2 ). 58 Regarding the results obtained with DES, it is evident that all of the systems present an identical spectrum to chitin, which was expected considering the results attained with FTIR. Additionally, these samples presented a crystallinity index identical to or higher than that of chitin.…”
Section: Resultssupporting
confidence: 65%
“… 17 , 56 , 57 The peak at 2θ ≈ 9–11° corresponds to amide I (−N–CO–CH 3 ), while the peak at 2θ ≈ 19–20° corresponds to amide II (−NH 2 ). 58 Regarding the results obtained with DES, it is evident that all of the systems present an identical spectrum to chitin, which was expected considering the results attained with FTIR. Additionally, these samples presented a crystallinity index identical to or higher than that of chitin.…”
Section: Resultssupporting
confidence: 65%
“…Regarding the inhibitory effect on P. ultimum, it was observed that CC maintained the oomycete in the lag stage for a more extended period than the UC. The above was attributed to the availability of the acetyl groups, attributed to a lower Icr and M W of CC than UC [51,52]. This effect is related to a higher number of protonated groups available to interact with the microbial cells [42,53].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that α-chitosan has a higher crystallinity index as compared to β-chitin. However, the crystallinity index for both forms is lower than the raw chitosan [21]. The crystallinity index will increase when the degree of deacetylation of chitosan increases [16].…”
Section: Crystalline Structurementioning
confidence: 91%
“…β-chitin has a parallel structure, which leads to the formation of the intramolecular hydrogen bond. γ-chitin consists of both antiparallel and parallel structure, as it is the combination of α-chitin and β-chitin [21].…”
Section: Crystalline Structurementioning
confidence: 99%
See 1 more Smart Citation